Performance and applications of quench melt-growth bulk magnets. (22nd January 2016) - Nariki, S; Teshima, H; Morita, M
Abstract: This paper describes the progress in quench melt-growth (QMG) bulk magnets, developed by the Nippon Steel & Sumitomo Metal Corporation, which consist of single crystalline RE123 phase and finely dispersed RE211 particles. QMG bulks can trap high magnetic fields. The field-trapping ability of QMG bulks is largely increased with an improvement in its  J c and size, promising the realization of various applications such as flywheel energy-storage systems, ship motors, NMR/MRI spectrometers, wind-power generators and so on. Intensive research has revealed that the optimal RE element is different depending on application requirements. Gd-QMG bulk is the most promising material for several high-field engineering applications. The trapped magnetic field of Gd-QMG bulk 60 mm in diameter at 77 K is twice as large as that of Y-QMG bulk with a similar size due to its excellent J c properties. The large Gd-based QMG bulks up to 150 mm in diameter are fabricated by incorporating the RE compositional gradient method. Compact NMR/MRI spectrometers are one of the promising applications of bulk superconductors. Eu-QMG bulks are suitable for NMR magnets. NMR applications require extremely homogeneous magnetic fields. In the Eu-system, the small paramagnetic moment of a Eu ion compared to a Gd ion improves the field homogeneity in the bulk. For the application of current leads, Dy-based QMG is available by utilizing a low thermal conductivity.